Axisymmetric granular flow on a bounded conical heap: Kinematics and size segregation. (18th May 2020) - Isner, Austin B.; Umbanhowar, Paul B.; Ottino, Julio M.; Lueptow, Richard M.
Graphical abstract: Highlights: Flowing layer depth is greater in 3D heaps than in wall bounded flows. Advection dominates over transport by segregation and diffusion in most cases. Flow is self-similar when scaled by local flowing layer depth and surface velocity. Continuum model predicts segregation of size-bidisperse mixtures in 3D heap flows. Abstract: Free surface flows of granular materials in bounded axisymmetric geometries such as a cylindrical silo are poorly understood. In particular, a detailed description of the local three-dimensional velocity field and predictive models for segregation are lacking. Here, the details of the kinematics of flow in a rising conical heap formed by a centrally fed mixture of spherical particles are investigated using Discrete Element Method (DEM) simulations in a wedge-shaped geometry with periodic azimuthal boundaries. The dependence of the streamwise and surface normal velocity components on the inlet flow rate and silo radius for size-bidisperse and monodisperse mixtures of glass spheres is characterized. Compared to a wedge with frictional sidewalls, the flowing layer is much thicker on average in the axisymmetric case. Using the scalings for kinematics obtained from the DEM simulations, a modified continuum advection-diffusion-segregation model accurately predicts steady-state segregation for axisymmetric conical heap flows of size-bidisperse mixtures.